Experimental characterization and theoretical investigation of Ce/Yb co-doped hydroxyapatites - Acar, Serdar; Kaygili, Omer; Ates, Tankut; Dorozhkin, Sergey, V; Bulut, Niyazi; Ates, Burhan; Hssain, Ala Hamd (Elsevier Science Sa, 2022)
In the present study, the effects of variable amounts of Yb addition on the structural, thermal, and in vitro biocompatibility properties of Ce-doped hydroxyapatite (HAp) samples synthesized via the wet chemical method were investigated. Besides, the prepared formulations were also modeled for making the theoretical investigations. The single-phase compositions were detected for all samples, and no formation of additional phases was observed. Doping with Yb was observed to produce some variations in the lattice parameters, unit cell volume, lattice strain, and lattice stress. While a decreasing trend in the crystallite size and crystallization percent with increasing Yb content was found, a gradual increase in the anisotropic energy density was observed. All samples were found to be thermally stable from room temperature to 1000 degrees C with negligible mass losses during heating. No significant morphological changes were caused by the addition of Yb. For all samples, the numerical values of (Ca + Ce + Yb)/P molar ratio were found to be close to that for stoichiometric HAp (1.67). It was observed that the increased Yb additive caused a decrease in cell viability values. A continuous decrease in the bandgap energy with the increasing amounts of Yb added to the Ce-based HAp structure was observed from the theoretical investigations. A sharp decrease in the cell viability of the Ce-based HAp was observed with the addition of Yb.
Keywords: Ion-substituted hydroxyapatite; Wet chemical method; Ce; Yb; Cell viability test